Thermodynamics of binary and ternary complexes of ascorbic acid and creatinine with Ag(I) - (:unkn) unknown (Freund Publishing House Ltd, 2003)
The stability constants of the 1:1 binary complexes of Ag(I) with creatinine and ascorbic acid and their 1:1:1 ternary complex and the protonation constants of the ligands were determined potentiometrically at a constant ionic strength of I = 0.10 mol L-1 (NaClO4) in aqueous solutions at 10.0, 15.0, 25.0 and 35°C. The thermodynamic parameters ΔGfo, Δfo andΔSfo reported for the formation reactions of the complexes. The enthalpy changes of all complexations are found to be negative but entropy changes positive. The driving force for the formation of Ag(I) - creatinine and Ag (I) creatinine - ascorbic acid complexes is the enthalpy decrease.